Improved beta-amyloid PET reproducibility using two-phase acquisition and grey matter delineation - Belohlavek, Otakar; Jaruskova, Monika; Skopalova, Magdalena; Szarazova, Gabriela; Simonova, Katerina (European journal of nuclear medicine and molecular imaging, 2019)
PURPOSE: We investigated whether the reproducibility of standard visual reporting (STD method) in flutemetamol (FMM) PET can be improved using a newly introduced method that uses grey matter edges derived from the perfusion phase (GM-EDGE method). METHODS: Two-phase FMM PET was performed in 121 patients with mild cognitive impairment. Five nuclear medicine physicians blindly and independently evaluated all late-phase scans, initially employing the STD method and later the GM-EDGE method. A five-point scale was used to express the degree of amyloid positivity, and a binary classification (positive/negative) was used in combination with subjective confidence (five-point scale). Multirater Fleiss' kappa, intraclass correlation coefficient (ICC) and inter-rater reliability (Cohen's kappa) were determined for the STD and GM-EDGE methods. RESULTS: The weighted Cohen's kappa values for the five-point measure of amyloid positivity ranged from 0.63 to 0.73 (median 0.70) for the STD method and from 0.76 to 0.89 (median 0.80) for the GM-EDGE method (ICC 0.84, 95% CI 0.79-0.88, for the STD method; 0.91, 95% CI 0.89-0.94, for the GM-EDGE method). The nonweighted Cohen's kappa value for the binary classification ranged from 0.73 to 0.93 (median 0.82) for the STD method and 0.90 to 0.97 (median 0.93) for the GM-EDGE method (Fleiss' kappa 0.82, 95% CI 0.77-0.88, for the STD method; 0.93, 95% CI 0.87-0.99, for the GM-EDGE method). The GM-EDGE method resulted in significantly greater subjective confidence in the readings of four physicians (p < 0.010). The binary classification was concordant among all five physicians in 80.8% of the scans using the STD method and in 91.6% of the scans using the GM-EDGE method (p = 0.016). CONCLUSION: The newly introduced GM-EDGE method was associated with significantly higher inter-rater agreement among physicians and higher subjective confidence in the reading. The method is easy to implement in clinical practice, especially when the perfusion phase is utilized clinically.
Keywords: dospělí; šedá hmota; Cognitive Dysfunction; Amyloid beta-Peptides; Positron Emission Tomography Computed Tomography; Adult; Gray Matter; lidé; amyloidní beta-protein; PET/CT; Aged, 80 and over; Male; počítačové zpracování obrazu; Aged; kognitivní dysfunkce; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Image Processing, Computer-Assisted; Humans